Обоснование применения гидрообъемно–механических трансмиссий на колесных тракторах путем экспериментального определения основных эксплуатационных характеристик гидрообъемной передачи - Самородов, Вадим Борисович; Деркач, Олег Игоревич; Шуба, Сергей Александрович; Шевцов, Вадим Михайлович; Митцель, Николай Александрович (НТУ "ХПИ", 2015)
Проведены экспериментальные исследования гидрообъемной передачи, входящей в состав гидрообъемно–механической трансмиссии, и получены основные параметры, характеризующие эффективность ее работы. В результате эксперимента подтверждена эффективность бесступенчатой гидрообъемно–механической трансмиссии и целесообразность ее использования на колесных тракторах различного тягового класса. Представлена кинематическая схема оригинального испытательного стенда трансмиссии и места подключения регистрирующих контрольно–измерительных приборов.

The analysis of domestic and foreign literature devoted Experimental study work double–split hydrostatic mechanical sending. Experimental studies of hydrostatic transmission, which is part of hydrostatic–mechanical transmission, and obtained basic parameters characterizing the efficiency of its work. The experiment confirmed the effectiveness of a continuously variable hydrostatic–mechanical transmission and the feasibility of its use in various wheeled tractors drawbar category. Presented kinematic scheme of the original transmission test stand and place of connection recording instrumentation. The results are of interest to researchers working in the field of study of structural schemes HVMT and are proof of the trend increase in the overall efficiency of hydrostatic transmissions by improving the design and use of modern materials in creating hydraulic machines.
The justification for applying hydrostatic–mechanical transmissions on wheeled tractors by experimental determination of basic performance of hydrostatic transmission
Keywords: бесступенчатая трансмиссия; экспериментальный стенд; ГОМТ; гидрообъемная передача; tractor; continuously variable transmission; hydrostatic transmission; performance; experimental stand